Effects of concentric and concentric-eccentric resistance training on speed and force in adult soccer players - Dominik Bokůvka; Tomáš Vencúrik; Firas Zghal; Serge Sebastien Colson; Ana Carolina Paludo (Scientific Reports)
Abstract This study investigated the effects of concentric and concentric-eccentric strength training on speed and strength performance in sub-elite soccer players. Thirty-four healthy Czech soccer players were randomly assigned to a concentric group (CONG, n = 13), concentric/eccentric group (ECCG, n = 12), or control group (CG, n = 9). All participants completed the study. Over an 8-week intervention period, the CONG and ECCG groups accomplished 16 training sessions focused on leg curl and leg extension exercises. Speed and strength assessments were performed at baseline and post-intervention. While no significant improvements were observed in speed performance (p > 0.05), both intervention groups demonstrated significant gains in strength parameters. One-repetition maximum (1RM) knee extension increased by 17.5% (CONG, p < 0.001) and 18.3% (ECCG, p < 0.001), and the 1RM knee flexion improved by 10.5% (CONG, p < 0.001) and 12.2% (ECCG, p < 0.001, compared to the CG, with moderate and clear effect sizes. ANOVA analysis revealed significant interaction effects for knee extension 1RM (p < 0.001), knee flexion 1RM (p = 0.022), and isometric knee extension of the dominant leg (p = 0.033). Despite these gains in muscle strength, speed performance showed only minor, non-significant changes, with the CONG group experiencing a 2.8% improvement in the 10-meter sprint. In conclusion, both concentric and concentric-eccentric strength training protocols effectively enhanced lower-limb strength in soccer players, with the concentric-eccentric approach showing slightly better results. However, neither training method significantly improved speed. Coaches should use concentric-eccentric exercises to enhance strength but consider other methods to boost speed and overall performance.